A Case Study on the Application of Hydroponics in Floriculture Sector - Chakraborty, Oendrilla; Sarkar, Dipayan; Kundu, Pratyay (Journal of Agricultural Extension Management, 2023)
Urbanization is increasing rapidly, with developing nations experiencing the fastest expansion. By 2030, there will be 4.98 billion metropolitan dwellers worldwide (UN, 2002). Urban horticulture is the practice of growing fruits, vegetables, flowers and herbs in confined spaces, such as unused plots, gardens, balconies and containers inside city homes (Zoysa, 2007). Food produced in urban spaces can harm the environment or food safety due to presence of contaminants, so the floriculture sector is being envisaged as an alternative there. Floriculture is an intensive type of agriculture with high income per unit area (Randhawa & Mukhopadhyay, 1986), making it a fast growing industry. Urban farming has faced difficulties due to the decline in land available per person, and will continue to shrink due to rapid urbanization, industrialization and iceberg melting. The presence of disease causing pathogens, nematodes, erosion etc. can cause serious problems to crop growth in soil based cultivation. Recently hydroponics has emerged as a potential alternative to produce green vegetables, flowers, seedlings, and herbs, mostly in periurban and urban areas. The primary benefit of soilless hydroponic cultivation is the year-round accessibility of green secure and healthy horticultural produce. To get a brief overview of the application of hydroponics system in floriculture crops globally as a tool of urban and periurban agriculture, a brief case study was carried out to trace the use of hydroponics in cut flowers like Rose, Gerbera, Chrysanthemum, Gladiolus, Lily etc and landscaping sector by studying research journals, books and the data was analyzed and represented to serve as baseline information to guide future research